In Vitro Assessment of Probiotic Properties in Lactobacillus Strains Isolated from Traditionally Fermented Thai Foods - Nitipan, Supachai; Boonloy, Kantida; Da-oh, Hudadini; Permpool, Jirawut; Saithong, Pramaun (Naresuan University Journal: Science and Technology (NUJST), 2021)
Traditionally fermented Thai foods are good sources for Lactobacilli isolation due to these food types include a wide variety of ingredients. A total of 82 Lactobacillus strains were preliminarily isolated from Pla-Som, Pla-Duk-Ra, Pla-Pang-Dang, Kung-Som, and Nham-Hed-Nang-Fa. Their 16S rDNA sequences showed homology to L. plantarum , L. lactis , L. amylovorus , L. casei , L. acidophilus , L. farciminis , and L. graminis . Gastrointestinal tract experimental found 10 isolates that can survive at pH 2.5 and 0.9% bile salt concentration. Remaining 4 isolates of L. plantarum (LpWP48/12, LpNH48/12) and L. acidophilus (LacKS48/15, LacWP48/22) had antagonistic activity against human pathogens including Staphylococcus aureus ( TISTR 746 ) , Escherichia coli ( TISTR 527 ) , Pseudomonas aeroginosa ( TISTR 357 ) , Salmonella Typhi, and Shigella dysentery . All four isolates were resistant to streptomycin, cefotetan, nalidixic acid, vancomycin, kanamycin, and methicillin . PCR analysis revealed positive identification of the bsh , atpD and mapA genes . The virulence - related genes cylA , ace , esp and gelE were found to be absent . As a result, L. plantarum (LpWP48/12 and LpNH48/12) and L. acidophilus (LacKS48/15 and LacWP48/22) showed potential as probiotic candidates and were safe to use as starter culture . Keywords: Lactic acid bacteria, Probiotics, Lactobacillus plantarum , Lactobacillus acidophilus , Traditionally fermented Thai food